Mood profile in patients with chronic diseases: its relationship with sociodemographic and clinical variables - Martínez-Soto, Joel (2022)
The objective of the present study is to document the mood profile and emotional disturbance indexes (EDI) in adult patients with cancer, renal insufficiency (RI), diabetes (D) and cardiovascular disease (CD). A total of 386 patients participated (cancer n = 96; RI n = 107; diabetes n = 91; CD n = 92) who self-reported their negative and positive mood states. The results evidence that the mood profile of the patients with CA and IR is similar in terms of their characterization and quantification, with IPE significantly lower than that of the patients with D and CD. On the other hand, compared with other groups, patients with CD present higher scores in all negative and positive dimensions of mood states. The influence of various sociodemographic and clinical variables on the adaptation and psychological response of patients is analyzed and discussed.